Application of Artificial Intelligence on Puzzle-8 Using Steepest Ascent Hill Climbing Algorithm - Y Yendrizal (IJISTECH (International Journal of Information System and Technology), 2022)
The Steepest-Ascent Hill Climbing algorithm is part of the implementation of artificial intelligence. To solve the case problem in Puzzle 8, an algorithm is needed to obtain the final result. Problems that often occur in this algorithm include, 1. the state of all adjacent boxes is worse or equal to its own state, 2. the state of all adjacent cities is the same as its own state, 3. local optimum which is due to the inability to use all operators at once. The way the Ascent Hill Climbing algorithm works is to start with the initial state, perform the test, if it is a goal then stop, and if not, continue with the current state as the initial state. The final result of this research is that there are 5 incorrect positions, after the completion process there are 8 correct puzzle positions according to the final state. Thus the test is stopped because it has obtained the final state.